A quality improvement programme to reduce hospital-acquired pressure injuries. Issue 3 (29th July 2020) - Gupta, Poonam; Shiju, Shiny; Chacko, Gracy; Thomas, Mincy; Abas, Asma; Savarimuthu, Indirani; Omari, Emad; Al-Balushi, Sara; Jessymol, Pulikana; Mathew, Sunitha; Quinto, Marife; McDonald, Ian; et al.
Abstract : Background: At Heart Hospital in Doha, Qatar (HH), 127 pressure injuries (PI) were identified in 2014, corresponding to an incidence of 6.1/1000 patient-days in first 4 months of 2014. Hospital-acquired pressure injury (HAPI) is one of the most common preventable complications of hospitalisation. HAPI significantly increases healthcare costs, including use of resources (dressings, support surfaces, nursing care time and medications). They also have a significant impact on patients in terms of pain, worsened quality of life, psychological trauma and increased length of stay. Working with the Institute for Healthcare Improvement (IHI), we implemented evidence-based practices in all In patient Units at HH with the aim of reducing the number of HAPIs by 60% within 2 years. Methods: In collaboration with IHI, our multidisciplinary clinical and risk assessment teams tested several changes and implemented a successful programme. The Surface, Skin inspection, Keep moving, Incontinence and Nutrition bundle was implemented. Signs, turning clocks and PI incidence 'calendars' were used in the units as reminders. Attention was paid to endotracheal tube ties in order to address device-related pressure injuries. Counts of HAPI (incidence) and number of PIs per 100 patients surveyed (prevalence) were prominently displayed. Changes were tested using the Plan-Do-Study-Act methodology. Statistical analysis using the independent t-test was applied to detect the significance of any difference in the incidence of HAPI before and after implementation of the changes. Results: The incidence of HAPI dropped from 6.1/1000 patient-days to 1.1/1000 patient-days, an 83.5% reduction. The prevalence, based on quarterly survey fell from 9.7/100 patients surveyed to 2.0/100 patients surveyed, a 73.4% decline. Conclusions: The interventions proved to be successful, reducing the incidence of PI by >80%. The outcomes were sustained over a 4-year period.